Measuring and Analyzing the Impact of Income Inequality on Sustainable Development a Panel Study of Selected Countries (2000-2023) - Ramzi Ibrahim, Roshna; Ali Ahmed, Younis (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The objective of this study is to investigate the impact that income inequality has on sustainable development and pinpoints economic and social indicators that are usually an indication of the poverty rate in a country. This study applies GMM/DPD estimation to analyze how income inequality affects economic and social sustainability, with special attention given to poverty rates in the selected countries. The results indicate that income inequality-as represented by the Gini coefficient-is positively influenced by aspects such as poverty, population, and unemployment rate; therefore, whenever there is an increase in these variables, inequality widens. The HDI, , in contrast, is considered to decrease income inequality. On top of that, the COVID-19 pandemic has increased inequality in the countries under observation. The study’s findings underscore the critical need for redistribution policies to reduce inequality and support sustainable development. In practical terms, governments in countries like Iraq, Iran, and Turkey could face challenges implementing progressive tax systems that target wealth redistribution. This study contributes to academic knowledge and provides valuable policy insights by applying a rigorous quantitative analysis-a panel data estimation-which can devise strategies that will help the region attain socioeconomic stability in a sustainable manner in the long run.